FUTUROLOGIST-PHILOSOPHER (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
In this article, the authors provide a brief overview of the scientific works and life path of Academician O. A. Togusakov. It is noted that his scientific research is aimed at a comprehensive scientific analysis of the conceptual essence, methodological principles and logical sequence of futurology. In the context of subject-object relations, the immanent essence of the phenomenon of human foresight is explored, with special attention paid to the variety of non-standard methods. In his research, he revealed the mechanism for determining the prognostic consciousness and cognition of people through the real process of their life. The general methodological principles and logical structure of foresight are considered from the point of view of its role in the cognitive process and significance in changing social practice, and most importantly, a person’s ability to see the future is considered as its main function.
Keywords: Togusakov O.A., scientific research, futurology, foresight, methodology, science, philosophy.